Application of bioisosterism in design of the semicarbazone derivatives as cruzain inhibitors: a theoretical and experimental study. Issue 6 (26th April 2017) - Vital, Drielli G.; Damasceno, Flávia S.; Rapado, Ludmila N.; Silber, Ariel M.; Vilella, Filipe S.; Ferreira, Rafaela S.; Maltarollo, Vinícius G.; Trossini, Gustavo H. G.
Abstract : A series of semicarbazone, thiosemicarbazone, and aminoguanidine derivatives were synthesized and tested as antitrypanosomal agents. The theoretical NMR of the compounds was calculated using molecular modeling techniques (density functional theory (DFT) calculations) and confirmed the formation of the compounds. The ability to inhibit cruzain and Trypanosoma cruzi epimastigote replication was evaluated. Cruzain inhibition ranged between 70 and 75% (100 μM), and IC50 values observed in epimastigote forms of T. cruzi ranged from 20 to 140 μM. Furthermore, the compounds did not present cytotoxicity at concentrations up to 50 and 250 μM in MTT tests. Molecular modeling studies were conducted using DFT method (B3LYP functional and the basis set 6-311G(d, p)) to understand the activity of the compounds, corroborating the observed cruzain inhibitory activity. In docking studies, the obtained analogs showed good complementarity with cruzain active site. In addition, docking results are in accordance with the susceptibility of these analogs to nucleophilic attack of the catalytic Cys25. Taken together, this study shows that this class of compounds can be used as a prototype in the identification of new antichagasic drugs.